Sistem Informasi Pengolahan Transaksi Bank Sampah: Sistem Informasi Pengolahan Transaksi Bank Sampah - -, Agustiena Merdekawati; Dhiana, Azis Sukma (SPECTA Journal of Technology, 2023)
Waste bank is a solution in waste management in Indonesia. The existence of this waste bank program can change people's minds to be more concerned about useless waste and goods that have value and price. Through the waste bank program, people can store waste and the waste can be exchanged for money that can be saved. However, in the management of the waste bank there are several problems, such as the community does not know information about becoming a customer or how to open a waste bank account, people who are already customers do not know the amount of their waste bank savings, because the system uses bookkeeping, customers do not know what type of waste price is set by the waste bank, and the waste bank manager still uses books for recording, can cause data loss, delays in processing data, so it is inefficient. Therefore we need a system to overcome this problem, namely by creating a waste bank processing information system. This system uses the waterfall model as a software development model and uses blackbox testing for testing.